Flow assurance in kumuje wet-gas pipeline: analysis of pigging solution to liquid accumulation (2018)
Liquid condensation in gas-condensate pipelines in a pronounced phenomenon in long transporting lines because of the composition of the gas which is highly sensitive to variations in temperature and pressure along the length of the pipeline. Hence, there is a resultant liquid accumulation in onshore wet-gas pipelines because of the pipeline profile. This accumulation which is a flow assurance problem can result to pressure loss, slugging and accelerated pipeline corrosion if not properly handled. Kumuje wet-gas pipeline is an onshore 19" carbon steel line which is approximately 70 km long in a hilly terrain with an elevation of 700 m above sea level. With the pipeline’s maximum design gas capacity and field operational capacity pegged at 165 and 135 MMSCFD respectively, this study was tasked with proposing an efficient pigging scheme for the removal of liquid inventory from the pipeline using the capacity of the slugcatcher as the basis for the scheme, also, factors which affected liquid accumulation and pigging efficiency was investigated using a dynamic multiphase simulator – OLGA. Using OLGA 2016.2, both steady and dynamic runs were carried out in other to investigate into some critical factors such as pipe profile and inclination, pig velocity, gas velocity, bypass pig leakage etc. that influence liquid condensation and holdup in a wet-gas pipeline. Of the three (3) pigging schemes considered, scheme 2 proved to be the ideal operational scheme because the surge volume (395 m3) generated by the pig is within the handling capacity of the slugcatcher (600 m3). Also, liquid holdup was seen to be strongly influenced by the pipe profile and a high flow-rate was observed to significantly reduce the volume of liquid held-up in the pipeline. Conclusively, OLGA simulator proved to be an excellent tool in simulating dynamic multiphase flow and predicting liquid holdup in wet-gas pipelines in a hilly terrain.